(untitled) (Bangladesh Journal of Botany, 2021)
Antioxidant and antibacterial activities of four underutilized fruits namely Jujube (Ziziphus mauritiana Lam.), Olive (Elaeocarpus serratus L.), Roselle (Hibiscus sabdariffa L.), and Taikor (Garcinia pedunculata Roxb.) commonly found in Bangladesh were evaluated. The highest total phenolic content (685.08 ± 27.65 mg GAE/100 ml) and total flavonoid content (148.18 ± 0.40 mg QE/100 ml) were found in Taikor extract, which compliance with its highest DPPH scavenging activity and antibacterial properties. It exerted a significantly higher (p ≤ 0.05) zone of inhibition against Escerichia coli, Staphylococcus spp. and Pseudomonas spp. than the other experimented fruit extracts. The antioxidant activity was found as Taikor (43.15 ± 1.61%)> Roselle (33.07 ± 1.61%) > Olive (28.68 ± 0.78%) > Jujube (24.81 ± 1.34%). Bacillus spp. are found to be more susceptible to the experimented sample extracts. Fruit samples studied may be utilized as potential sources of natural antioxidants and antibacterial compounds, and their extracts may be used as natural biopreservatives to extend the shelf life of foodstuffs. Bangladesh J. Bot. 50(4): 1035-1039, 2021 (December)